An Interdisciplinary Bibliometric Review of the Symbiotic Relationship between Business Intelligence and Artificial Intelligence - Loso Judijanto; I Wayan Karang Utama; Nita Priska Ambarita; Indra Permana (Eastasouth Institute, 2023)
This research conducts an interdisciplinary bibliometric review to explore the symbiotic relationship between Business Intelligence (BI) and Artificial Intelligence (AI). Utilizing advanced bibliometric tools, we analyze a comprehensive dataset extracted from reputable databases, encompassing articles that meet predefined inclusion criteria. The study reveals thematic clusters, influential documents, and core keywords shaping the discourse within the BI-AI landscape. Thematic clusters highlight the multidisciplinary nature of research, ranging from the impact of AI on finance to business model innovation and sustainability. The top-ten cited documents provide a snapshot of seminal works guiding academic and practical understanding, while keyword analysis illuminates the central themes and areas of emphasis. The cross-analysis of these elements offers a nuanced view of the evolving landscape of BI-AI integration. The findings not only contribute to academic scholarship but also provide practical insights for organizations navigating the dynamic intersection of BI and AI.